Case report: Fatal lung hyperinflammation in a preterm newborn with SARS-CoV-2 infection - Aguilar-Caballero, Daniela; Capcha, Jose M. C.; Caballero, Veronica; Young, Karen C.; Duara, Shahnaz; Borchetta, Michael; Gonzalez, Ivan; Saad, Ali G.; Webster, Keith A.; Shehadeh, Lina A.; Bandstra, Emmalee S.; Schmidt, Augusto F. (Frontiers in Pediatrics, 2023)
Vertical transmission of SARS-CoV-2 from mother to fetus is widely accepted. Whereas most infected neonates present with mild symptoms or are asymptomatic, respiratory distress syndrome (RDS) and abnormal lung images are significantly more frequent in COVID-19 positive neonates than in non-infected newborns. Fatality is rare and discordant meta-analyses of case reports and series relating perinatal maternal COVID-19 status to neonatal disease severity complicate their extrapolation as prognostic indicators. A larger database of detailed case reports from more extreme cases will be required to establish therapeutic guidelines and allow informed decision making. Here we report an unusual case of a 28 weeks’ gestation infant with perinatally acquired SARS-CoV-2, who developed severe protracted respiratory failure. Despite intensive care from birth with first line anti-viral and anti-inflammatory therapy, respiratory failure persisted, and death ensued at 5 months. Lung histopathology showed severe diffuse bronchopneumonia, and heart and lung immunohistochemistry confirmed macrophage infiltration, platelet activation and neutrophil extracellular trap formation consistent with late multisystem inflammation. To our knowledge, this is the first report of SARS CoV-2 pulmonary hyperinflammation in a preterm newborn with fatal outcome.